Distributional Consequences of Asset Price Inflation in the Euro Area - Klaus Adam; Panagiota Tzamourani (University of Mannheim, Department of Economics, 2015)
We study the distributional consequences of housing price, bond price and equity price increases for Euro Area households using data from the Household Finance and Consumption Survey (HFCS). The capital gains from bond price and equity price increases turn out to be concentrated among relatively few households, while the median household strongly benefits from housing price increases. The capital gains from bond price increases (relative to household net wealth) do not correlate with household net wealth (or income). Bond price increases thus leave net wealth inequality largely unchanged. In contrast, equity price increases largely benefit the top end of the net wealth (and income) distribution, thus amplify net wealth inequality. Housing price increases display a hump shaped pattern over the net wealth distribution, with the poorest and richest households benefitting least. With regard to the latter finding there exists considerable heterogeneity across Euro Area countries.
urn:nbn:de:bsz:180-madoc-396970
Keywords: D31; E21; E52; E58; 330; asset price inflation; wealth redistribution